2016
DOI: 10.1016/j.hpb.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Qualities and characteristics of successfully matched North American HPB surgery fellowship candidates

Abstract: Results of this survey provide useful and practical information for trainees considering applying to an HPB fellowship program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Our finding is similar to a study of Hepato-pancreato-biliary (HPB) fellowships, which found ABSITE in the bottom third of importance rating and ranked below interview, LoR, and research experience during applicant evaluation. 10 Despite this, the average ABSITE percentile of applicants in their study was above the 75 th percentile. The authors suggested that, “As these qualities [high ABSITE scores] are so common amongst the matching fellows, the low rating may be a reflection of the limited usefulness in differentiating candidates and not of their importance to becoming a successful HPB surgeon.” 10 Indeed, it is possible that a similar trend exists in the CGSO population.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our finding is similar to a study of Hepato-pancreato-biliary (HPB) fellowships, which found ABSITE in the bottom third of importance rating and ranked below interview, LoR, and research experience during applicant evaluation. 10 Despite this, the average ABSITE percentile of applicants in their study was above the 75 th percentile. The authors suggested that, “As these qualities [high ABSITE scores] are so common amongst the matching fellows, the low rating may be a reflection of the limited usefulness in differentiating candidates and not of their importance to becoming a successful HPB surgeon.” 10 Indeed, it is possible that a similar trend exists in the CGSO population.…”
Section: Discussionmentioning
confidence: 78%
“…10 Despite this, the average ABSITE percentile of applicants in their study was above the 75 th percentile. The authors suggested that, “As these qualities [high ABSITE scores] are so common amongst the matching fellows, the low rating may be a reflection of the limited usefulness in differentiating candidates and not of their importance to becoming a successful HPB surgeon.” 10 Indeed, it is possible that a similar trend exists in the CGSO population. The majority of respondents in our study indicated a minimum score to be met prior to offering an interview and many of them set this score above the 50 th percentile.…”
Section: Discussionmentioning
confidence: 78%
“…The AHPBA, in conjunction with the Fellowship Council, currently offers 26 fellowship positions across the USA and Canada. Twenty-one programs offer HPB only training (11 one-year programs and 10 two-year programs), three offer HPB training embedded within the SSO training model, and two offer HPB training that is embedded [15]. In the South American region (Argentina and Brazil) can be found 14 HPB fellowship programs registered in IHPBA.…”
Section: Postgraduate Hpb Trainingmentioning
confidence: 99%
“…Recently, Baker et al define the qualities and characteristics of successfully matched HPB surgical fellows. They concluded that the most important qualities in an HPB fellow, as ranked by both program directors and fellows, are interpersonal and perceived operative skills, closely followed by perceived fund of knowledge and communication skills [15].…”
Section: Postgraduate Hpb Trainingmentioning
confidence: 99%
“…1 Previous studies have sought to define factors associated with matriculation to hepatopancreaticobiliary (HPB), pediatric, and endocrine surgery fellowships using survey studies or through review of single-institution data. 710 However, surveys or single institution reviews do not capture the entire applicant pool for any given specialty and therefore are subject to inherent biases. To provide a comprehensive and objective view of application to CGSO fellowship training, we obtained data on all applicants from the Electronic Residency Application System (ERAS).…”
mentioning
confidence: 99%